Community paramedicine—cost–benefit analysis and safety with paramedical emergency services in rural areas: scoping review protocol - Hege Selnes Haugdahl; Marianne Lysne; Odd Eirik Elden; Oddvar Uleberg (BMJ Open)
Introduction Community paramedicine models have been developed around the world in response to demographic changes, healthcare system needs and reforms. The traditional role of the paramedic has primarily been to provide emergency medical response and transportation of patients to nearby medical facilities. As a response to healthcare service gaps in underserved communities and the growing professionalisation of the workforce, the role of community paramedicine has evolved as a new model of care. A community paramedicine model in one region might address other healthcare needs than a model in another region. Various terms are also in use for community paramedicine providers, with no consensus on the definition for community paramedics, although the definition used by the International Roundtable on Community Paramedicine has been widely accepted. We aimed to examine the current knowledge and possibly identify gaps in the research/knowledge base for cost–benefit analysis and safety concerning community paramedicine in rural areas using a scoping review methodology.Methods and analysis This scoping review will follow the methodology developed by Arksey and O’Malley and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews. In October 2020, we will search electronic databases (MEDLINE via PubMed, CINAHL, Cochrane and Embase) and the reference lists of key studies to identify studies for inclusion. The selection process is in two steps. First, two reviewers will independently screen identified articles for title and abstracts and, second, perform a full-text review of eligible studies for inclusion. Studies focusing on community paramedicine in rural areas, which include cost–benefit analysis or safety evaluation, will be included.Ethics and dissemination The data used are available from publicly secondary sources, therefore this study will not require ethical review. The results will be disseminated through peer-reviewed publication.